Pregnancy Complicated with Severe Recurrent Aortic Coarctation: A Case Report - Celal Yavuz; Hatice Ender Soydinc; Güven Tekbaş; Oguz Karahan (Case Reports in Vascular Medicine)
A 23-year-old primigravida was referred to our clinic for evaluation of high blood pressure (BP) in her 16th week of gestation. She had an operation to repair congenital aortic coarctation and patent ductus arteriosus 8 years ago. On physical examination the blood pressure in upper extremity was 155/95 and in lower extremity was 90/55 mmHg, and heart rate was 93 beats/min. Transthoracic echocardiography showed narrowing of the descending aorta, the diameter of the aortic arch was 10.60 mm and an echocardiographic gradient was 96 mmHg. During the pregnancy (from 16 weeks to 38 weeks) BP was regulated with metoprolol. Cesarean section delivery was applied at 38 weeks of gestation. There was no complication in postpartum period. Spinal anesthesia application was used for caesarean section intervention and healthy female baby was delivered with the APGAR scores of 10/10. Herein the diagnosis of aortic coarctation is reviewed and the management when found during pregnancy is discussed.